(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve high school students’ critical thinking skills through a history writing workshop. The background of this program lies in the challenges of history learning at the secondary level, which is often dominated by rote memorization, resulting in students’ lack of analytical ability and low engagement in constructing historical narratives. The workshop was implemented at SMA Negeri 1 Baturraden with 30 participants from the Youth Scientific Work group. The methods used combined lectures on the principles of historical and essay writing with hands-on training in source analysis and essay development. The activity was conducted in three sessions covering the introduction of historical writing and essay structure, verification and analysis of historical sources, and the practice of writing historical essays. The results showed that participants demonstrated significant improvement in critical thinking, particularly in source evaluation, argument development, and the ability to present historical narratives logically and systematically. The workshop not only strengthened students’ historical literacy but also contributed to character building by fostering responsibility, independence, and reflective attitudes. This program is expected to serve as a model for innovative history learning and can be replicated in other schools to enhance students’ critical and creative competencies in line with 21st-century skills.